Identity in multicultural context - Hidasi, Judit (Studia Mundi – Economica, 2015)
The issue of identity is raised in the context of multiculturalism. Inspite of the ongoing process of globalization or better as a consequence of it in the domain of culture instead of homogenization weratherwitness a tendency of cultural diversification. Societal and socio- psychological motivations and drives behind this phenomenon will be disscussed – with particular focus on identity. Impacts and challenges of cultural diversification will be looked at with respect to the variety and efficiency of ways they are handled in diverse societies and cultures. Although no common and general remedies exist for handling issues of identity neither on the level of the individual nor on that of the collective, the role of education and media will be emphasized in the dimension of conflict-resolution, idea-formation and community cooperation.